Light‐Emitting Diodes: Control of LED Emission with Functional Dielectric Metasurfaces (Laser Photonics Rev. 14(1)/2020). Issue 1 (8th January 2020) - Khaidarov, Egor; Liu, Zhengtong; Paniagua‐Domínguez, Ramón; Ha, Son Tung; Valuckas, Vytautas; Liang, Xinan; Akimov, Yuriy; Bai, Ping; Png, Ching Eng; Demir, Hilmi Volkan; Kuznetsov, Arseniy I.
Abstract : In article number 1900235 by Zhengtong Liu, Volkan Demir, Arseniy I. Kuznetsov, and co‐workers, full wavefront control of LED radiation in an integrated fashion is achieved by combining resonant cavities and metasurfaces. This method endows LED sources with the advanced functionalities enabled by metasurfaces, such as lensing, complex beam shaping and holography, opening new venues for compact, functional light sources.